A FULL MISSILE HOMING SYSTEM DESIGN BASED ON PROPORTIONAL NAVIGATION GUIDANCE LAW AND ELECTRO-OPTICAL TRACKING SYSTEM (Journal of Engineering, 2008)
Generally, the homing systems are majorly constructing from three components: the guidance law, the target tracking system, and the missile flight control system. Therefore, in this paper, we construct our homing system from the following components: the proportional navigation guidance law which is considered as the guidance scheme for most homing missile systems, the electro-optical tracking system, and a tail controlled missile. And subsequently complete mathematical derivations and the demand transfer function formulations of all these three components have been introduced. The proposed homing system is capable to pursuit and hit any target just by specifying the required missile flight time. A SIMULINK software program has been built mainly from four subsystems to simulate the operation of this homing system, and the simulation results show clearly the efficient performance of the proposed homing system under any probable disturbance